Presence of gastrointestinal parasites in swine and human of four swine production farms in Cundinamarca- Colombia - María F Mendoza-Gómez; Adriana Pulido-Villamarín; Angélica Barbosa-Buitrago; Moisés Aranda-Silva (Revista MVZ Cordoba, 2015)
Objectives. Determine the presence and the type of endoparasites with zoonotic potential in swine and human of two technified and two semi-technified farms in the department of Cundinamarca, Colombia. Materials and methods. Three serial samplings of feces were taken in a pen row within intervals of 15 days, in two technified and two semi-technified farms in different age groups distributed as follows: pregnant-sows, nursing-females, boars, weaners, suckling-piglets, and growing-pig. By means of informed consent thirty-three people agreed to enter the study. Thirty-three samples from men and women of different ages were received. The pool and individual samples of fecal were evaluated by direct analysis, qualitative flotation and sedimentation techniques and modified ZiehlNeelsen stain. Results. For the porcine population, on the average, the results obtained from both technified farms showed that Balantidium coli (42%), Endolimax nana (21.9%) and Iodamoeba bütschlii (7.8%) were the most common parasites. In semi-technified farms they were: Entamoeba coli (40%), Endolimax nana (35%), Iodamoeba bütschlii (25%) and Balantidium coli (5%). By means of the test chi2 it is possible to conclude that there is a significant difference between the parasites species and the type of farm. The results obtained in human showed the presence of parasites as: E. coli (42.2%), Entamoeba hystolitica/dispar (12.1%), E. nana (9.1%), B. coli (9.1%), I. bütschlii (3.0%) and Blastocystis hominis (3.0%). Conclusions. The presence of parasites such as Balantidium coli, Endolimax nana, Iodamoeba bütschlii and Entamoeba coli in swine and human suggests a possible rotation of parasitic species between hosts.